The Effect of Cupping Therapy on Blood Pressure in Elderly Patients - Kistan; Najman (Babali Health, 2022)
Introduction: Hypertension is understood as the silent killer as it frequently appears without symptoms and is a major cause of cardiovascular disease. The elderly is a group who is vulnerable to being diagnosed with cardiovascular disease. Cupping therapy is a popular alternative treatment option performed by the community. Over time, it encourages nurses to entirely evidence the benefits of cupping therapy. The objective of this study is to determine the effect of cupping therapy on reducing blood pressure in the elderly. Methods: This research was conducted by employing a method in the form of a quasi-experimental one-group pretest-posttest. Researchers examined blood pressure before cupping therapy and calculated it again 30 minutes after cupping therapy. The sample administered was 15 elderly patients with cupping at Al Ghaffar Care, Bone Regency, which were selected by administering purposive sampling technique. Results: After conducting statistical analysis by employing the paired sample T-test, the systolic pressure was obtained a significant value (p 0.001 < 0.05) with an average decrease in systolic pressure of 5.133 mmHg and a significant diastolic pressure was acquired (p 1,000 > 0.05). The results signify that there is an effect between a decrease in systolic pressure but no effect on diastolic pressure before and after cupping therapy. Conclusion: In order to allow for a reduction in the dose of antihypertensive medications administered and lower the danger of drug dependence, cupping therapy can be thought of as an alternative therapy and adjunct therapy in patients with high blood pressure.